Application of vibro‐acoustography in prostate tissue imaging. Issue 2 (14th January 2013) - Alizad, Azra; Mehrmohammadi, Mohammad; Mitri, Farid G.; Davis, Brian J.; Sebo, Thomas J.; Mynderse, Lance A.; Kinnick, Randall R.; Greenleaf, James F.; Fatemi, Mostafa
Abstract : Purpose: : To evaluate the potential of the imaging modality vibro‐acoustography (VA) for imaging of the prostate. Methods: : Excised cadaver prostate specimens were embedded in tissue mimicking gel to simulate the properties of surrounding soft tissues. The samples were imaged at various depths using a laboratory prototyped VA imaging system. The recorded signals were used for offline processing and image reconstruction. In a selected subgroup of tissue samples, conventional ultrasound (B‐mode) and x‐ray imaging were performed for further analysis, evaluation, and validation of the VA images. Results: : The imaging results of prostate tissue samples indicate the capability of VA imaging to detect prostatic nodules and lesions. In the prostate sample with an adenocarcinoma, the lesion appears with a clear contrast with respect to its surrounding tissue. The VA images could also identify the presence of calcifications deep inside the prostate tissue. Further, quantifications of the imaging results demonstrate that VA imaging has higher sensitivity to detect the calcifications compared to conventional ultrasound imaging. VA is also capable of visualizing prostatic tissue structures and in some cases can identify the anatomical zones. More specifically, the observed higher texture level in peripheral zones demonstrates the ability of VA to differentiate between prostatic anatomical zones. Conclusions: : Imaging results of ex vivo prostate tissues, reveals the potency of VA as a promising tool to detect abnormalities, delineate tissue structures and anatomical zones, and locate calcifications. The results of this pilot study suggest that in vivo VA imaging of the prostate may be of clinical utility.